The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12565-008-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Weapon-related traumas of human skeletons from Yuigahama Chusei Shudan Bochi, Japan

Abstract: The Yuigahama Chusei Shudan Bochi site (AD: twelfth to thirteenth centuries), located along the seashore of the southern end of Kamakura City in Japan, and has yielded a mass grave containing hundreds of human crania. The purpose of this study is to document cut marks on crania made by an edged weapon, paying specific attention to individuals who may exhibit scratch marks, and to understand the variability of weapon-related traumas in the medieval period in Japan. The observation leads to tentative findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…Several preceding studies have shown that human skeletons from medieval Japan exhibited traumatic injuries related to violence, such as gashes, decapitations, blows, stabbing, and scratches (Suzuki et al, 1956;Morimoto, 1987;Morimoto and Hirata, 1992;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010. The results of this study demonstrated the presence of weapon-related traumas on the cranium and limb bones.…”
Section: Weapon-related Traumassupporting
confidence: 59%
See 3 more Smart Citations
“…Several preceding studies have shown that human skeletons from medieval Japan exhibited traumatic injuries related to violence, such as gashes, decapitations, blows, stabbing, and scratches (Suzuki et al, 1956;Morimoto, 1987;Morimoto and Hirata, 1992;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010. The results of this study demonstrated the presence of weapon-related traumas on the cranium and limb bones.…”
Section: Weapon-related Traumassupporting
confidence: 59%
“…Comparative samples for this study were cited from the literature on paleodemography (Nagaoka et al, 2006(Nagaoka et al, , 2012bNagaoka andHirata, 2007, 2008), dental caries (Sakura, 1964;Fujita, 1995;Ohshima, 1996;Todaka et al, 2003), enamel hypoplasia (Sawada, 2010), and violent behavior (Suzuki et al, 1956;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010Nagaoka, 2012) (Table 1). The chronological ages used in the comparative samples are the Jomon (14500-300 BC), Yayoi (300 BC-300 AD), medieval (1185-1573 AD), and Edo (1603-1687 AD) periods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medieval Kamakura and early-modern Kumejima peoples Intensive paleodemographic research has been performed and has revealed that the medieval Kamakura people were not long lived (Nagaoka et al, 2006;Nagaoka and Hirata, 2008). In addition, many weapon-related traumas were found among the skeletal remains from medieval Kamakura (Suzuki et al, 1956;Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010. However, there have been few studies on the life activity patterns of these people.…”
Section: People From Okhotsk Culturementioning
confidence: 99%